2006
DOI: 10.1073/pnas.0605748103
|View full text |Cite
|
Sign up to set email alerts
|

Role of molecular charge and hydrophilicity in regulating the kinetics of crystal growth

Abstract: The composition of biologic molecules isolated from biominerals suggests that control of mineral growth is linked to biochemical features. Here, we define a systematic relationship between the ability of biomolecules in solution to promote the growth of calcite (CaCO 3) and their net negative molecular charge and hydrophilicity. The degree of enhancement depends on peptide composition, but not on peptide sequence. Data analysis shows that this rate enhancement arises from an increase in the kinetic coefficient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

21
335
0
1

Year Published

2008
2008
2018
2018

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 244 publications
(357 citation statements)
references
References 55 publications
(74 reference statements)
21
335
0
1
Order By: Relevance
“…This may be a reason that the switch effect has not been revealed in the previous studies because only the long polyAsp is applied. It is also confirmed experimentally that the short polyAsp segments have a similar role with Asp monomer in the biomimetic studies despite of that the efficiencies may be different (28). Because the function of polyAsp or the other peptides is sensitive to its length (43), the use of Asp monomer is simple and reasonable in the current in vitro model system.…”
Section: Resultssupporting
confidence: 52%
See 1 more Smart Citation
“…This may be a reason that the switch effect has not been revealed in the previous studies because only the long polyAsp is applied. It is also confirmed experimentally that the short polyAsp segments have a similar role with Asp monomer in the biomimetic studies despite of that the efficiencies may be different (28). Because the function of polyAsp or the other peptides is sensitive to its length (43), the use of Asp monomer is simple and reasonable in the current in vitro model system.…”
Section: Resultssupporting
confidence: 52%
“…Herein, combined with the FT-IR results, it is reasonable to assume that, Asp-rich biomolecules may switch on the crystallization reaction. However, the previous studies of biomimetic mineralization show that Asp-rich peptides and other organic matrices often inhibit crystallization despite that a few of them can accelerate the nucleation at low concentrations (27)(28)(29)(30). It is even demonstrated that the cooperation of magnesium and associated proteins can stabilize the amorphous phases more (4,10,31).…”
Section: Resultsmentioning
confidence: 99%
“…Several studies have examined the interaction of organic molecules with calcite's surface under different circumstances, [29][30][31] but the inherent complexity of the system and the large number of variables able to influence calcite's surface dynamics often result in conflicting findings. 23,32 Here we use high-resolution amplitude-modulation atomic force microscopy (AM-AFM) in liquid 33,34 to follow in real-time and with nanometer precision the evolution of calcite (101 ത 4) coated with stearic acid (SA) and exposed to different saline solutions.…”
Section: Introductionmentioning
confidence: 99%
“…Their effects on ACC precipitation/ crystallization and the crystal morphologies are consistent with the charge of the side group, where the negatively charged (under the experimental conditions) side groups of Asp and Glu are considered to interact with the Ca 2+ ions at the crystal surface. 45 All of the amino acids studied are negatively charged under the experimental conditions, where the pI values for Asp, Glu, Asn and Val are 2.9, 3.2, 5.4 and 6 respectively. Modeling of the interaction of Asp molecules with calcite surfaces has also shown that these molecules preferentially bind to the symmetry related acute step edges via specific stereochemistry.…”
Section: Discussionmentioning
confidence: 99%
“…Soluble additives can strongly influence calcite morphologies through preferential association with the acute or obtuse step edges, or pinning of step movement. 43 45 The effect of Asp on calcite growth has been particularly well studied, where preferential binding to the acute step edges ultimately gives rise to elongated particles with highly roughened sides, that are capped at each apex with three, smooth {104} faces. 13, 46 At higher supersaturations and additive concentrations calcite can also form polycrystalline particles.…”
Section: Scanning Electron Microscopy (Sem)mentioning
confidence: 99%